Estimates of Earnings Returns by Field of Study for For-Profit Schools and Community Colleges - Christopher Jepsen; Peter Mueser; Kenneth Troske; Kyung-Seong Jeon (Center for Economic Studies and ifo Institute (CESifo), 2023)
This paper estimates labor-market returns for students pursuing certificates or associate's degrees in eight broad fields of study at community colleges and for-profit institutions. The data contain 400,000 students beginning their studies between 2005 and 2012 in one state. We estimate two-step models to address recent econometric concerns with two-way fixed effects models. Our analyses show important differences in return by field, with similar patterns for for-profit schools and community colleges. Apart from those studying in health fields, returns are generally greater for those attending for-profit schools than those attending community colleges. Higher estimated overall returns for for-profit schools are not primarily due to differences in areas of study.
Keywords: J24; I26; 330; postsecondary education; labor-market returns; for-profit schools